ANALYSIS OF THE IMPLEMENTATION AND PREPARATION OF FOUNDATION FINANCIAL REPORTS BASED ON ISAK 35 CASE STUDY ON THE AL-MUSLIH ISLAMIC BOARDING SCHOOL FOUNDATION (Prosiding dan Call Paper Widya Wiwaha, 2024)
The Al-Muslih Islamic Boarding School Foundation, in preparing its financial statements, only records cash inflows and outflows and has not yet implemented the provisions of ISAK 35, which serves as the basis for the preparation of financial statements for non-profit entities. ISAK 35 is an accounting standard that regulates the recognition, measurement, and disclosure of transactions within non-profit organizations. The implementation of ISAK 35 is crucial to ensure that financial statements are prepared transparently and reflect the actual financial condition. The purpose of this study is to analyze the implementation of ISAK 35 and to prepare financial statements using a case study of the Al-Muslih Islamic Boarding School Foundation in Karawang Regency. This research is descriptive qualitative-analytic in nature. Data collection techniques include observation, interviews, and documentation. The data used consists of secondary data in the form of cash receipts and disbursement reports, and primary data obtained through interviews and observations. The data analysis method applied is descriptive qualitative analysis. Based on the research results, it can be concluded that the Al-Muslih Islamic Boarding School Foundation has not yet applied ISAK 35 in its financial reporting and only records cash inflows and outflows. This indicates a deficiency in the presentation and disclosure of information, which does not comply with established standards. The research results provide a model of financial statements according to ISAK 35, which includes a statement of financial position, statement of comprehensive income, statement of changes in net assets, and a cash flow statement.
Keywords: Financial Reports; ISAK 35; Preparation of Islamic Boarding School Financial Reports.